Intra- and Inter- Subject Variability of High Field fMRI Digit Maps in Somatosensory Area 3b of New World Monkeys - Zhang, Na (2009)
This study evaluates the intra- and inter- subject variability of digit maps in area 3b of anesthetized squirrel monkeys. Maps were collected using high field Blood Oxygenation Level Dependent (BOLD) fMRI. BOLD responses to individual digit stimulations were mapped and their response properties (location, area of activation, % signal change, time to peak response) were compared within and across imaging sessions separated by up to 20 months. During single digit stimulation using a block design, the spatio-temporal response of the BOLD signal for individual runs within and across sessions and animals was well conserved, with a time to peak BOLD response of 20 ± 4 sec. The variability in the center of BOLD activation in area 3b was 0.41 ± 0.24 mm (mean ± SD) across individual 5–7 minutes runs within a scanning session and 0.55 ± 0.15 mm across sessions. The average signal change across all animals, runs and sessions was 0.62 ± 0.38 %, and varied 32% within and 40% across sessions. In a comparison of the stability and reproducibility of the area of single digit activation obtained using three approaches, use of a fixed statistical threshold (p<10(−5)) yielded an average area of 4.8 ± 3.5 mm(2) (mean ± SD), adaptive statistical thresholding 1.32 ± 1.259 mm(2) (mean ± SD), and combined fixed statistical and adaptive BOLD signal amplitude 4.4 ± 2.5 mm(2) (mean ± SD) across image runs and sessions. The somatotopic organization was stable within animals across sessions, while across animals, there was some variation in overall activation pattern and inter-digit distances. These results confirm that BOLD activation maps of single digits in area 3b as characterized by activation center, signal amplitudes, and temporal profile are very stable. The activation sizes determined by various criteria are the most variable measure in this preparation, but adaptive statistical thresholding appears to yield the most stable and reproducible maps. This study serves as a baseline assessment of the limits imposed on the detection of plastic changes by experimental variations of the digit BOLD fMRI activation maps in normal animals, and as an indicator of the likely performance limits in human studies.